Metal-doped molybdenum disulfide composite super-smooth coating and preparation method thereof

By using dual-target cosputtering technology to form a metal-doped molybdenum disulfide composite coating in MoS2 coating, the problem that MoS2 coating in the prior art cannot have both a dense columnar structure and a low friction coefficient is achieved. High wear resistance and low friction performance in open atmospheric environments, suitable for aerospace transportation systems.

CN119121122AInactive Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411243509.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-28
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing MoS2 coatings cannot have a dense columnar structure and a low coefficient of friction, especially in open atmospheric environments, resulting in poor tribological performance.

Method used

The metal transition layer is formed by sputtering the metal target on the substrate surface using a DC power supply, and the molybdenum disulfide target is sputtered in an inert atmosphere using a pulse power supply to form a metal-doped molybdenum disulfide composite coating, and is prepared by co-sputtering of the dual-target material. Metal-doped molybdenum disulfide composite superslip coating realizes vertical symbiosis and strong interaction between metal nanoparticles and MoS2 sheet layer, forming a "T" array Ag-MoS2 low hanging bond film.

Benefits of technology

A smoother and denser deposited film is obtained, with a dense columnar structure and low friction coefficient, which improves the internal order and oxidation resistance of the film. It is suitable for aerospace transportation in the "earth-space-sky" atmosphere of the atmosphere and vacuum alternating atmosphere environment. System, the steady-state average friction coefficient is minimized in open atmospheric environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005029951730000011
    Figure HDA0005029951730000011
  • Figure HDA0005029951730000012
    Figure HDA0005029951730000012
  • Figure HDA0005029951730000021
    Figure HDA0005029951730000021
Patent Text Reader

Abstract

The invention discloses a metal-doped molybdenum disulfide composite super-smooth coating and a preparation method thereof, and belongs to the technical field of composite super-smooth coatings. The invention discloses a preparation method which comprises the following steps: sputtering metal palladium on a substrate by adopting a direct-current power supply to obtain a metal transition layer, depositing a molybdenum disulfide target on the metal transition layer by adopting a pulsed power supply, and preparing a metal-doped molybdenum disulfide composite super-smooth coating by adopting a double-target co-sputtering mode. The metal nanoparticles and the vertically oriented MoS2 sheet layer in the film are co-grown and have strong interaction to form the T-shaped array type Ag-MoS2 low dangling bond film, dangling bonds can be encapsulated to the maximum extent, the internal order degree of the film is improved, and the number of dangling bonds is reduced; meanwhile, the density and the oxidation resistance are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite super-slip coatings, and in particular relates to a metal-doped molybdenum disulfide composite super-slip coating and a preparation method thereof. Background Art

[0002] As an excellent solid lubricant, MoS2 coating is widely used in vacuum and space fields, such as spacecraft moving parts and rolling bearings, due to its high wear resistance, high durability and extremely low friction coefficient. However, the tribological behavior of MoS2 coating shows strong environmental sensitivity, and the tribological performance degrades in an open atmospheric environment. To solve these problems, adding a small amount of metal elements to the MoS2 coating can effectively prevent the oxidation of MoS2-based films, greatly improve the durability of MoS2 coatings, and improve the reusability of space transportation systems. Metal-doped MoS2 composite super-slip coatings are composed of two main parts: a metal transition layer and a metal MoS2 composite coating.

[0003] Transition metal chalcogenides, such as molybdenum disulfide and tungsten disulfide, are solid lubricating materials for space applications. Transition metal chalcogenides have a specific layered crystal structure, and the "sandwich" stacked layers are bonded by weak van der Waals forces, with extremely low shear strength, so that they can show a low friction coefficient. Generally, molybdenum disulfide has good tribological properties in vacuum, inert atmosphere and low-humidity air. With the increase of ambient humidity or the increase of oxygen content in the environment, the tribological properties deteriorate. This mainly depends on the crystal orientation of molybdenum disulfide (vertical orientation, or edge plane orientation, type I; parallel orientation, or reference plane orientation, type II). Type I usually has a columnar structure, but its friction coefficient is relatively high; the surface of type II film is dense and shows a low friction coefficient, but its film is relatively loose. Therefore, how to prepare a molybdenum disulfide lubricating film that has the advantages of both types I and II, that is, a dense columnar structure and a low friction coefficient, is an important problem to be solved for those skilled in the art. Summary of the invention

[0004] The purpose of the present invention is to provide a metal-doped molybdenum disulfide composite super-slip coating and a preparation method thereof, so as to solve the technical problem that the existing coating cannot have the advantages of both Type I and Type II.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention discloses a method for preparing a metal-doped molybdenum disulfide composite super-slip coating, comprising the following steps:

[0007] Using a DC power supply, a metal target is sputtered on the substrate surface in an inert atmosphere to form a metal transition layer;

[0008] Subsequently, a pulse power supply is turned on while a DC power supply is turned on to sputter a metal target, and a pulse power supply is used to sputter a molybdenum disulfide target in an inert atmosphere to form a metal molybdenum disulfide composite coating, thereby obtaining a metal-doped molybdenum disulfide composite super-slippery coating.

[0009] Furthermore, before the metal target is sputtered, the substrate is ultrasonically cleaned with alcohol and acetone for 30 to 40 minutes, and then cleaned with argon plasma.

[0010] Furthermore, the process parameters of the argon plasma cleaning are:

[0011] Vacuum to 10 -4 Pa, introduce argon gas flow rate of 13-15sccm, adjust the working gas pressure to 9-10Pa, set the pulse bias to -400V, the duty cycle to 50-60%, the frequency to 60-70KHz, and bias cleaning for 20min.

[0012] Furthermore, the process parameters for sputtering the metal target on the substrate surface using a DC power supply are:

[0013] Vacuum to 1×10 -5 Pa, working gas pressure 0.4~0.8Pa, sputtering power 50~70W, 90~110sccm of argon gas is introduced into the vacuum chamber, and the sputtering time is 10~20min.

[0014] Furthermore, the type of the metal target is one of Ag target, Au target, Cu target, Ti target, Cr target or W target.

[0015] Furthermore, the process parameters of sputtering the metal molybdenum disulfide target using a pulse power supply in an inert atmosphere are: vacuuming to 1×10 -5 Pa, 90-120 sccm of argon is introduced into the vacuum chamber, the working gas pressure is 0.4-0.8 Pa, the sputtering power is 190-210 W, the pulse bias is set to -1200 V, the duty cycle is 50-60%, the frequency is 60-70 KHz, and the sputtering time is 88-92 min.

[0016] The invention also discloses a metal-doped molybdenum disulfide composite super-slip coating prepared by the preparation method.

[0017] Furthermore, the metal-doped molybdenum disulfide composite super-slip coating comprises a metal deposition layer and a metal molybdenum disulfide composite coating; the metal deposition layer and the metal molybdenum disulfide composite coating are sequentially arranged on the substrate from bottom to top.

[0018] Furthermore, the metal deposition layer belongs to a layered-island growth mode.

[0019] Furthermore, the metal molybdenum disulfide composite coating has a Thornton-type structure; the MoS2 flakes in the metal molybdenum disulfide composite coating are edge-plane oriented inside the coating and are reference-plane oriented at the top.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The invention discloses a method for preparing a metal-doped molybdenum disulfide composite super-lubricating coating, which comprises the following steps: using a direct current power supply to sputter metal palladium on a substrate to obtain a metal transition layer, and simultaneously using a pulse power supply to deposit a molybdenum disulfide target on the metal transition layer, and adopting a double-target co-sputtering method to prepare the metal-doped molybdenum disulfide composite super-lubricating coating. Compared with the prior art, this method can obtain a smoother and denser deposited film, which has the advantages of both types I and II, namely, a molybdenum disulfide lubricating film with a dense columnar structure and a low friction coefficient.

[0022] Furthermore, this preparation method can make the metal nanoparticles co-grow with the vertically oriented MoS2 sheets inside the film, and have a strong interaction to form a "T"-shaped array Ag-MoS2 low dangling bond film, which can maximize the encapsulation of dangling bonds, improve the internal order of the film, and reduce the number of dangling bonds; at the same time, it ensures density and antioxidant properties.

[0023] The present invention also discloses a metal-doped molybdenum disulfide composite super-slip coating prepared by the above-mentioned preparation method, including a metal transition layer and a metal molybdenum disulfide composite coating arranged in sequence from bottom to top on a substrate, the metal transition layer belongs to a typical layered-island growth mode, the metal molybdenum disulfide composite coating has a Thornton-type structure, the MoS2 layer is edge-plane oriented inside the film and reference-plane oriented at the top; according to relevant experimental results, the change of the substrate temperature affects the crystallization degree and nucleation rate of the film, and as the temperature increases, the surface of the film gradually transitions from "worm-like" and "granular" to "acupuncture-like" morphological characteristics; the coating of the present invention has good tribological properties and is suitable for a repeatable aerospace transportation system in an atmospheric vacuum alternating atmosphere environment of "ground-air-sky". According to actual measurements, the film friction and wear performance test was carried out on the surface of a mirror stainless steel sheet (type 316L). When the substrate temperature was 200°C, the steady-state average friction coefficient value in an open atmospheric environment reached a minimum of 0.0024.

[0024] Furthermore, the deposition of the metal transition layer is to improve the bonding strength between the film layer and the substrate, effectively overcome the film-substrate mismatch problem, and can greatly reduce the internal stress of the film and improve the bonding strength between the film and the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1The surface and cross-sectional SEM of the Ag-doped molybdenum disulfide composite super-slip coating prepared in the atmospheric environment of the present invention at a substrate temperature of room temperature to 300°C;

[0026] Among them: a1, a2: room temperature; b1, b2: 50℃; c1, c2: 100℃; d1, d2: 200℃; e1, e2: 250℃; f1, f2: 300℃;

[0027] Figure 2 There are three different film growth modes;

[0028] Figure 3 The AFM morphology of the Ag-doped molybdenum disulfide composite super-slip coating prepared in the atmospheric environment of the present invention at a substrate temperature of room temperature to 300°C (the inset is a roughness variation trend diagram);

[0029] Figure 4 The friction test data of the Ag-doped molybdenum disulfide composite super-slip coating prepared in the atmospheric environment of the present invention at a substrate temperature of room temperature to 300°C;

[0030] Where: a-friction coefficient curve; b-average friction coefficient value;

[0031] Figure 5 The experimental data of the Ag-doped molybdenum disulfide composite super-slip coating prepared in the atmospheric environment of the present invention;

[0032] Among them: a-comparison of friction coefficient curves of pure MoS2 and VO-Ag / MoS2 at 200℃ and local enlarged views of running-in period and superlubrication stage (illustration); b-schematic diagram of friction and wear test; c-schematic diagram of superlubrication mechanism. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0040] Example 1

[0041] The metal-doped molybdenum disulfide composite super-slip coating of this embodiment includes a metal transition layer (Ag, Au, Cu, Ti, Cr, W, etc.) and a metal molybdenum disulfide composite coating arranged in sequence from bottom to top on a substrate; in this embodiment, the substrate is a mirror stainless steel sheet (type 316L), and in this embodiment, an Ag-doped MoS2 composite coating is prepared, and the test time is 30 minutes;

[0042] A method for preparing the metal-doped molybdenum disulfide composite super-slip coating as described above comprises the following steps:

[0043] Step 1: Place the substrate in a mixed solution of alcohol and acetone in a ratio of 1:1 for ultrasonic cleaning, dry it, and then place it on the sample rotating table in the vacuum chamber of a high-power micro-pulse magnetron sputtering coating machine. Close the upper cover of the vacuum chamber and evacuate the vacuum chamber. Perform ultrasonic cleaning for 30 minutes to clean the impurities and substances soluble in alcohol and acetone on the surface of the substrate.

[0044] Step 2: Perform argon ion cleaning on the substrate; evacuate to 10 -4 Pa, introduce argon gas flow rate of 13-15 sccm, adjust the working gas pressure to 9-10 Pa, set the pulse bias to -400 V, the duty cycle to 50-60%, the frequency to 60-70 KHz, and bias cleaning for 20 minutes;

[0045] Step 3: Open the mechanical pump and bypass valve to pump the low vacuum to within 10Pa; then close the bypass valve, open the front valve, turn on the molecular pump, and when the molecular pump speed reaches 4-5 thousand revolutions, open the gate valve to pump the high vacuum to 10 -4 Pa; finally, Ar is introduced, the argon flow rate is controlled by adjusting the argon flowmeter, and then the gate valve is adjusted to adjust the air pressure in the vacuum chamber to the working pressure;

[0046] Step 4: Deposit the metal transition layer: introduce argon gas into the vacuum chamber, adjust the working gas pressure, turn on the substrate heating power supply, set the substrate temperature, turn on the DC power supply, adjust the appropriate parameters, sputter the silver target, and form a silver deposition layer on the substrate surface; specifically, when depositing the metal transition layer, evacuate to 1×10 -5 Pa, deposition pressure was 0.6 Pa, sputtering power was 60 W, argon gas was introduced into the vacuum chamber at 100 sccm, and sputtering time was 15 min;

[0047] Step 5: Metal MoS2 composite coating: introduce argon gas into the vacuum chamber and set the substrate temperature; keep the DC power on while turning on the RF power and adjust the appropriate parameters; after ignition, turn on the bias power and start preparing the composite film layer; specifically, evacuate to 1×10 -5 Pa, 108 sccm of argon was introduced into the vacuum chamber, the deposition pressure was 0.6 Pa, the sputtering power was 200 W, the pulse bias was set to -1200 V, the duty cycle was 50-60%, the frequency was 60-70 KHz, and the sputtering time was 90 min;

[0048] from Figure 1 (a1), Figure 1 (a2) and Figure 3 It can be seen from RT that at room temperature, the film surface has fragmented protrusions and a large number of wrinkles; Figure 4 a and Figure 4 As can be seen from b, the friction coefficient first decreases slightly, and after a short period of time, the friction coefficient reaches a minimum value; then the friction coefficient value rises sharply and remains at around 0.02 during the remaining test period.

[0049] Example 2

[0050] The metal-doped molybdenum disulfide composite super-slip coating of this embodiment includes a metal transition layer (Ag, Au, Cu, Ti, Cr, W, etc.) and a metal molybdenum disulfide composite coating arranged in order from bottom to top on the substrate. In this embodiment, the substrate is a mirror stainless steel sheet (316L type); in this embodiment, an Ag-doped MoS2 composite coating is prepared; the test time is 30 minutes;

[0051] A method for preparing the metal-doped molybdenum disulfide composite super-slip coating as described above comprises the following steps:

[0052] Step 1: Place the substrate in a mixed solution of alcohol and acetone in a ratio of 1:1 for ultrasonic cleaning, dry it, and then place it on the sample rotating table in the vacuum chamber of a high-power micro-pulse magnetron sputtering coating machine. Close the upper cover of the vacuum chamber and evacuate the vacuum chamber. Perform ultrasonic cleaning for 30 minutes to clean the impurities and substances soluble in alcohol and acetone on the surface of the substrate.

[0053] Step 2: Perform argon ion cleaning on the substrate; evacuate to 10 -4 Pa, introduce argon gas flow rate of 13-15 sccm, adjust the working gas pressure to 9-10 Pa, set the pulse bias to -400 V, the duty cycle to 50-60%, the frequency to 60-70 KHz, and bias cleaning for 20 minutes;

[0054] Step 3: Open the mechanical pump and bypass valve to pump the low vacuum to within 10Pa; then close the bypass valve, open the front valve, turn on the molecular pump, and when the molecular pump speed reaches 4-5 thousand revolutions, open the gate valve to pump the high vacuum to 10 -4 Pa; finally, Ar is introduced, the argon flow rate is controlled by adjusting the argon flowmeter, and then the gate valve is adjusted to adjust the air pressure in the vacuum chamber to the working pressure;

[0055] Step 4: Deposit the metal transition layer: introduce argon gas into the vacuum chamber, adjust the working gas pressure, turn on the substrate heating power supply, and set the substrate temperature; turn on the DC power supply, adjust the appropriate parameters, sputter the silver target, and form a metal silver deposition layer on the substrate surface; specifically, when depositing the metal transition layer, evacuate to 1×10 -5 Pa, deposition pressure was 0.6 Pa, sputtering power was 60 W, argon gas was introduced into the vacuum chamber at 100 sccm, and sputtering time was 15 min;

[0056] Step 5: Deposition of metal molybdenum disulfide composite coating: introduce argon gas into the vacuum chamber and set the substrate temperature; keep the DC power supply on while turning on the RF power supply and adjust the appropriate parameters; after ignition, turn on the bias power supply and start preparing the composite film layer; specifically, evacuate to 1×10 -5Pa, 108 sccm of argon was introduced into the vacuum chamber, the deposition pressure was 0.6 Pa, the sputtering power was 200 W, the pulse bias was set to -1200 V, the duty cycle was 50-60%, the frequency was 60-70 KHz, and the sputtering time was 90 min;

[0057] from Figure 1 (b1), Figure 1 (b2) and Figure 350℃, it can be seen that when the substrate temperature is 50℃, the particle distribution on the film surface is relatively scattered and sparse, with some larger particles doped in between. The cross-sectional structure is uneven, loose and porous with low density. Figure 4 It can be seen that the friction coefficient has remained stable after a small increase, indicating that the initial substrate heating greatly improved the defects on the film surface and increased the friction life of the film.

[0058] Example 3

[0059] The metal-doped MoS2 composite super-slip coating of this embodiment includes a metal transition layer (Ag, Au, Cu, Ti, Cr, W, etc.) and a metal MoS2 composite coating arranged in order from bottom to top on the substrate. In this embodiment, the substrate is a mirror stainless steel sheet (316L type); Ag-doped MoS2 composite coating is prepared in this embodiment; the test time is 30 minutes

[0060] A method for preparing the metal-doped molybdenum disulfide composite super-slip coating as described above comprises the following steps:

[0061] Step 1: Place the substrate in a mixed solution of alcohol and acetone in a ratio of 1:1 for ultrasonic cleaning, dry it, and then place it on the sample rotating table in the vacuum chamber of a high-power micro-pulse magnetron sputtering coating machine. Close the upper cover of the vacuum chamber and evacuate the vacuum chamber. Perform ultrasonic cleaning for 30 minutes to clean the impurities and substances soluble in alcohol and acetone on the surface of the substrate.

[0062] Step 2: Perform argon ion cleaning on the substrate; evacuate to 10 -4 Pa, introduce argon gas flow rate of 13-15 sccm, adjust the working gas pressure to 9-10 Pa, set the pulse bias to -400 V, the duty cycle to 50-60%, the frequency to 60-70 KHz, and bias cleaning for 20 minutes;

[0063] Step 3: Open the mechanical pump and bypass valve to pump the low vacuum to within 10Pa; then close the bypass valve, open the front valve, turn on the molecular pump, and when the molecular pump speed reaches 4-5 thousand revolutions, open the gate valve to pump the high vacuum to 10 -4 Pa; finally, Ar is introduced, the argon flow rate is controlled by adjusting the argon flowmeter, and then the gate valve is adjusted to adjust the air pressure in the vacuum chamber to the working pressure;

[0064] Step 4: Deposit the metal transition layer: introduce argon gas into the vacuum chamber, adjust the working gas pressure, turn on the substrate heating power supply, and set the substrate temperature; turn on the DC power supply, adjust the appropriate parameters, sputter the silver target, and form a metal silver deposition layer on the substrate surface; specifically, when depositing the metal transition layer, evacuate to 1×10 -5 Pa, deposition pressure was 0.6 Pa, sputtering power was 60 W, argon gas was introduced into the vacuum chamber at 100 sccm, and sputtering time was 15 min;

[0065] Step 5: Deposition of metal molybdenum disulfide composite coating: introduce argon gas into the vacuum chamber and set the substrate temperature; keep the DC power supply on while turning on the RF power supply and adjust the appropriate parameters; after ignition, turn on the bias power supply and start the preparation of the composite film layer; specifically, evacuate to 1×10 -5 Pa, 108 sccm of argon was introduced into the vacuum chamber, the deposition pressure was 0.6 Pa, the sputtering power was 200 W, the pulse bias was set to -1200 V, the duty cycle was 50-60%, the frequency was 60-70 KHz, and the sputtering time was 90 min;

[0066] from Figure 1 (c1), Figure 1 (c2) and Figure 3100° show that as the substrate temperature rises to 100°C, the film surface presents a typical loose "worm-like" structure with many holes and gaps, with a single length of 400-500nm and a loose surface structure; Figure 1 (d1), (d2), Figure 3200° and Figure 4 It can be seen that when the substrate temperature is 200°C, the average friction coefficient value decreases to 0.0025, the roughness value is the smallest, the surface is smooth, the particles are more densely compacted, and the particles are closely connected, which is conducive to lubrication. Figure 1 (e1), Figure 1 (e2) and Figure 3250° show that when the substrate temperature further increases to 250°C, the degree of crystallization is serious, and a sparse "needle-like" structure with a size of about 1.3μm appears on the surface of the film. The cross-sectional structure is loose and there are large holes, which hinder the lubrication of the film. Figure 3 It can be seen that when the substrate is heated from 50℃ to 250℃, the roughness increment is relatively small, increasing from 4.558nm to 5.532nm. The friction coefficient remains at a stable stage during the entire test period, without showing an obvious upward or downward trend, indicating that the surface structure of the film is stable and the tribological performance is good when the substrate temperature is maintained at 100-250℃.

[0067] Example 4

[0068] The metal-doped molybdenum disulfide composite super-slip coating of this embodiment includes a metal transition layer (Ag, Au, Cu, Ti, Cr, W, etc.) and a metal molybdenum disulfide composite coating arranged in sequence from bottom to top on a substrate; in this embodiment, the substrate is a mirror stainless steel sheet (316L type); in this embodiment, an Ag-doped MoS2 composite coating is prepared; the test time is 30 minutes;

[0069] A method for preparing the metal-doped molybdenum disulfide composite super-slip coating as described above comprises the following steps:

[0070] Step 1: Place the substrate in a mixed solution of alcohol and acetone in a ratio of 1:1 for ultrasonic cleaning, dry it, and then place it on the sample rotating table in the vacuum chamber of a high-power micro-pulse magnetron sputtering coating machine. Close the upper cover of the vacuum chamber and evacuate the vacuum chamber. Perform ultrasonic cleaning for 30 minutes to clean the impurities and substances soluble in alcohol and acetone on the surface of the substrate.

[0071] Step 2: Perform argon ion cleaning on the substrate; evacuate to 10 -4 Pa, introduce argon gas flow rate of 13-15 sccm, adjust the working gas pressure to 9-10 Pa, set the pulse bias to -400 V, the duty cycle to 50-60%, the frequency to 60-70 KHz, and bias cleaning for 20 minutes;

[0072] Step 3: Open the mechanical pump and bypass valve to pump the low vacuum to within 10Pa; then close the bypass valve, open the front valve, turn on the molecular pump, and when the molecular pump speed reaches 4-5 thousand revolutions, open the gate valve to pump the high vacuum to 10 -4 Pa; finally, Ar is introduced, the argon flow rate is controlled by adjusting the argon flowmeter, and then the gate valve is adjusted to adjust the air pressure in the vacuum chamber to the working pressure;

[0073] Step 4: Deposit the metal transition layer: introduce argon gas into the vacuum chamber, adjust the working gas pressure, turn on the substrate heating power supply, and set the substrate temperature; turn on the DC power supply, adjust the appropriate parameters, sputter the silver target, and form a metal silver deposition layer on the substrate surface; specifically, when depositing the metal transition layer, evacuate to 1×10 -5 Pa, deposition pressure was 0.6 Pa, sputtering power was 60 W, argon gas was introduced into the vacuum chamber at 100 sccm, and sputtering time was 15 min;

[0074] Step 5: Deposition of metal molybdenum disulfide composite coating: introduce argon gas into the vacuum chamber and set the substrate temperature; keep the DC power supply on while turning on the RF power supply and adjust the appropriate parameters; after ignition, turn on the bias power supply and start the preparation of the composite film layer; specifically, evacuate to 1×10 -5Pa, 108 sccm of argon was introduced into the vacuum chamber, the deposition pressure was 0.6 Pa, the sputtering power was 200 W, the pulse bias was set to -1200 V, the duty cycle was 50-60%, the frequency was 60-70 KHz, and the sputtering time was 90 min;

[0075] from Figure 1 (f1), (f2) and Figure 3300° show that when the substrate reaches 300°C, the degree of crystallization is too serious, the surface smoothness of the film is seriously reduced, and a large number of "needle puncture" island structures are distributed, with a size of about 2μm. In addition, each complete "needle puncture" is distributed independently, and the gap between it and other "needle punctures" is large. Figure 3 It can be seen that the maximum roughness Ra reaches 9.06nm; from the film cross section, it can be seen that the film begins to "collapse", resulting in a decrease in film thickness; Figure 4 It can be seen that the friction coefficient continued to rise in the first 20 minutes, reaching a maximum value of 0.09. After maintaining a high value for a short period of time, the friction coefficient began to decrease to about 0.03 and tended to be flat.

[0076] It can be seen that when preparing composite films, the thermodynamic driving force plays a vital role in the random condensation of atoms on the growth surface. During the sputtering deposition of thin films, after the sputtered atoms reach the substrate surface, there will be movement processes such as attachment, desorption and migration. This series of movement processes is directly related to the substrate temperature. When the substrate temperature is low, the surface molecular activation energy is low, and migration and diffusion processes are not easy to occur, resulting in a decrease in the crystallinity of the film. Most of the film is amorphous or has a smaller grain size, and the grain boundaries increase. When the substrate temperature is high, the surface molecular activation energy is high and it is very easy to diffuse, so the film has good crystallization performance. The film exhibits a polycrystalline structure and the grain size becomes larger, and a discontinuous island film structure is easy to form. It can be seen that the substrate temperature has a great influence on the surface roughness.

[0077] The relative motion of two objects will produce friction. The generally accepted definition is that if the friction coefficient is less than 0.01, it is super-lubricating. In short, when the substrate temperature is between 50℃ and 250℃, μ<0.01, and the tribological properties are excellent, it means that the appropriate substrate temperature greatly improves the lubrication properties of the film, while too high a substrate temperature will destroy the internal structure of the film and weaken the lubrication effect of the film. When the substrate temperature is between 50℃ and 250℃, the coating has good super-lubricating ability.

[0078] See also Figure 2 Initially, the wettability between the film and the substrate is good, the deposited atoms tend to bond with the substrate atoms, the film expands and grows along the substrate surface, and then the growth mode changes from the layered mode to the island mode. And as the substrate temperature increases, the Ag atoms deposited on the surface have a certain diffusion ability, and begin to aggregate, and the nucleation size gradually increases, which is more conducive to the growth of the island mode.

[0079] See also Figure 5 It can be seen that the metal-doped molybdenum disulfide super-slippery film Ag nanoparticles of the present invention can reduce the environmental sensitivity of friction behavior by self-assembly to form a core-shell structure under the induction of friction. Mechanical external force causes the partial peeling of MoS2 and metal cluster-like nanocrystal columns, and the peeled metal nanocrystals induce MoS2 to curl up, forming nano-balls with a shell-core structure. The rolling effect of the nano-balls transforms sliding friction into rolling friction, and the nano-balls reduce the real contact area during the friction process. The non-commensurate contact sharply reduces the friction coefficient, which is super-slip on a macro scale.

[0080] The present invention provides a preparation method of a metal-doped molybdenum disulfide composite super-slip coating material, which can make Ag nanoparticles co-grow with vertically oriented MoS2 sheets inside the film, generate strong interactions, and form a "T"-shaped array Ag-MoS2 low-dangling bond film, which can maximally encapsulate dangling bonds, improve the orderliness inside the film, and reduce the number of dangling bonds. At the same time, the density and oxidation resistance are guaranteed; at the same time, the present invention aims at the environmental sensitivity of the low-friction behavior of the MoS2-based coating, and in order to solve the key lubrication problem of my country's repeatable space-to-ground round-trip aerospace transportation system, provides a metal-doped molybdenum disulfide composite super-slip coating material, which has high wear resistance, high durability and extremely low friction coefficient in the "ground-air-space" atmospheric vacuum alternating atmosphere environment.

[0081] The mechanism of the present invention is as follows:

[0082] The nc Ag (Stranski-Krastanov growth mode) grown in a "layer-island" shape on the substrate can act as a nucleation active induction site, inducing preferential adsorption nucleation at the edge of MoS2, regulating the order of the MoS2 film and the (002) basal plane orientation, and constructing a "T"-shaped array Ag-MoS2 low dangling bond film. The few MoS2 sheets on the surface of the film are parallel oriented, and the nc Ag grows together with the vertically oriented MoS2 (002) sheets inside the film. It can maximize the encapsulation of dangling bonds, improve the internal order of the film, and reduce the number of dangling bonds.

[0083] The substrate temperature affects the degree of crystallization and nucleation rate of the film. As the temperature increases, the film surface gradually transitions from "worm-like" and "granular" to "needle-like" morphological features. The increase in substrate temperature reduces the steady-state average friction coefficient of the film and improves the tribological properties of the film. As the substrate temperature rises from room temperature to 200°C, the film surface becomes smooth and uniform, which makes the roughness of the film continue to decrease, which is conducive to friction lubrication, and the friction life of the film continues to increase; when the substrate temperature increases from 200°C to 300°C, large pieces of tissue appear on the film surface, causing the roughness of the film to increase sharply and the friction life of the film to be severely shortened.

[0084] Ag nanoparticles self-assemble to form a core-shell structure under friction induction, which can reduce the environmental sensitivity of friction behavior. Mechanical external force causes partial exfoliation of MoS2 and metal cluster nanocrystal columns, and the exfoliated metal nanocrystals induce MoS2 to curl up, forming nano-balls with a core-shell structure. The rolling effect of the nano-balls transforms sliding friction into rolling friction, and the nano-balls reduce the real contact area during the friction process. The non-commensurate contact sharply reduces the friction coefficient, which is super-slip on a macro scale.

[0085] The coating of the present invention has good tribological performance and is suitable for a repeatable aerospace transportation system in an atmospheric vacuum alternating atmosphere environment of "ground-air-space". According to actual measurements, a film friction and wear performance test was conducted on the surface of a mirror stainless steel sheet (type 316L). When the substrate temperature was 200°C, the steady-state average friction coefficient value in an open atmospheric environment reached a minimum of 0.0024.

[0086] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a metal-doped molybdenum disulfide composite super-slip coating, characterized in that: The following steps are involved: Using a DC power supply, a metal target is sputtered on the substrate surface in an inert atmosphere to form a metal transition layer; Subsequently, a pulse power supply is turned on while a DC power supply is turned on to sputter a metal target, and a pulse power supply is used to sputter a molybdenum disulfide target in an inert atmosphere to form a metal molybdenum disulfide composite coating, thereby obtaining a metal-doped molybdenum disulfide composite super-slippery coating.

2. The method for preparing a metal-doped molybdenum disulfide composite super-slip coating according to claim 1, characterized in that: Before the metal target is sputtered, the substrate is ultrasonically cleaned with alcohol and acetone for 30 to 40 minutes, and then cleaned with argon plasma.

3. The method for preparing a metal-doped molybdenum disulfide composite super-slip coating according to claim 2, characterized in that: The process parameters of the argon plasma cleaning are: Vacuum to 10 -4 Pa, introduce argon gas flow rate of 13-15sccm, adjust the working gas pressure to 9-10Pa, set the pulse bias to -400V, the duty cycle to 50-60%, the frequency to 60-70KHz, and bias cleaning for 20min.

4. The method for preparing a metal-doped molybdenum disulfide composite super-slip coating according to claim 1, characterized in that: The process parameters for sputtering a metal target on the substrate surface using a DC power supply are: Vacuum to 1×10 -5 Pa, working gas pressure 0.4~0.8Pa, sputtering power 50~70W, 90~110sccm of argon gas is introduced into the vacuum chamber, and the sputtering time is 10~20min.

5. The method for preparing a metal-doped molybdenum disulfide composite super-slip coating according to claim 1, characterized in that: The metal target is one of Ag target, Au target, Cu target, Ti target, Cr target or W target.

6. The method for preparing a metal-doped molybdenum disulfide composite super-slip coating according to claim 1, characterized in that: The process parameters of sputtering the metal molybdenum disulfide target using a pulse power supply in an inert atmosphere are: vacuuming to 1×10 - 5 Pa, 90-120 sccm of argon is introduced into the vacuum chamber, the working gas pressure is 0.4-0.8 Pa, the sputtering power is 190-210 W, the pulse bias is set to -1200 V, the duty cycle is 50-60%, the frequency is 60-70 KHz, and the sputtering time is 88-92 min.

7. A metal-doped molybdenum disulfide composite super-slip coating, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. The metal-doped molybdenum disulfide composite super-slip coating according to claim 7, characterized in that: The metal-doped molybdenum disulfide composite super-slip coating comprises a metal deposition layer and a metal molybdenum disulfide composite coating; the metal deposition layer and the metal molybdenum disulfide composite coating are sequentially arranged on a substrate from bottom to top.

9. The metal-doped molybdenum disulfide composite super-slip coating according to claim 8, characterized in that: The metal deposition layer belongs to a layer-island growth mode.

10. The metal-doped molybdenum disulfide composite super-slip coating according to claim 8, characterized in that: The metal molybdenum disulfide composite coating has a Thornton-type structure; the MoS2 flakes in the metal molybdenum disulfide composite coating are oriented in the edge plane inside the coating and in the reference plane at the top.

Citation Information

Patent Citations

  • Preparation method of MoS2 composite thin film with high hardness and loss abrasion on surface of substrate

    CN103060765A

  • Metal-doped molybdenum disulfide super-smooth film and preparation method thereof

    CN113088911A

  • Metal-doped molybdenum disulfide high-temperature-resistant composite film and preparation method thereof

    CN114959558A

Cited By

  • Method for improving quality of magnetron sputtering molybdenum disulfide film and improving friction performance through precious metal micro-doping

    CN120006229A

  • A method for improving the quality of magnetron sputtering molybdenum disulfide film and enhancing the friction performance by noble metal micro-doping

    CN120006229B

  • Controllable preparation method of environment self-adaptive lubricating homotype heterostructure film

    CN120555968A